Conductive Biomaterials as Bioactive Wound Dressing for Wound Healing and Skin Tissue Engineering - Rui Yu (SpringerOpen, 2021)
Abstract Conductive biomaterials based on conductive polymers, carbon nanomaterials, or conductive inorganic nanomaterials demonstrate great potential in wound healing and skin tissue engineering, owing to the similar conductivity to human skin, good antioxidant and antibacterial activities, electrically controlled drug delivery, and photothermal effect. However, a review highlights the design and application of conductive biomaterials for wound healing and skin tissue engineering is lacking. In this review, the design and fabrication methods of conductive biomaterials with various structural forms including film, nanofiber, membrane, hydrogel, sponge, foam, and acellular dermal matrix for applications in wound healing and skin tissue engineering and the corresponding mechanism in promoting the healing process were summarized. The approaches that conductive biomaterials realize their great value in healing wounds via three main strategies (electrotherapy, wound dressing, and wound assessment) were reviewed. The application of conductive biomaterials as wound dressing when facing different wounds including acute wound and chronic wound (infected wound and diabetic wound) and for wound monitoring is discussed in detail. The challenges and perspectives in designing and developing multifunctional conductive biomaterials are proposed as well.